Impact of Revenue Administration on Revenue Performance in Nigerian Local Governments - Oladimeji, Kazeem Adebayo (Journal of Techno-Social, 2023)
This study examines the integrated impact of the revenue administration system on revenue performance in Nigerian local governments. The revenue administration system comprises tax compliance, taxpayer registration, and audit effectiveness, which collectively influence revenue performance. Using a quantitative approach, data was collected through questionnaire administration among selected local government employees in Nigeria’s Kwara Central Senatorial District. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized for data analysis to assess the relationships between the revenue administration system components and revenue performance. The findings reveal that tax compliance, taxpayer registration, and audit effectiveness significantly impact revenue performance in Nigerian local governments. Higher levels of tax compliance and an inclusive taxpayer base led to increased revenue collection, enabling local governments to finance public services and development initiatives. Moreover, effective tax audits deter potential tax evaders, promoting voluntary compliance and contributing to enhanced revenue generation. This study’s approach provides a comprehensive understanding of the factors influencing revenue performance at the local government level. The findings have practical implications for policymakers and revenue authorities, suggesting strategies to strengthen the revenue administration system for improved revenue outcomes and socio-economic development in Nigerian local governments.